Community Participation through Environmental Investment to Develop Ecotourism in Bedengan Forest Ecotourism, Malang Regency - Candra, Fitri; Abidin , Zainul; Atikawati, Dini; Sudaryanti, Sri; Hidayati, Bunga; Fatih, Ahmad Nuril Fuad Al; Malik, Muhammad Adam (Journal of Community Based Environmental Engineering and Management, 2024)
Bedengan Forest Ecotourism, Malang Regency is one of sustainable tourism destinations, a tourism area that is environmentally friendly and based on ecology which is managed by Lembaga Kemitraan Desa Pengelola Hutan/Forest Management Village Partnership Institute (LKDPH). This research discusses about community especially tourist motivation to participate through environmental investments that have an impact on preserving the forest environment in Bedengan. The objectives of this research are to find out the priority tourist attributes of Bedengan Forest Ecotourism and estimating the value of the community's Willingness to Pay (WTP) for retribution. The analytical methods used quantitative descriptive and contingent valuation method. The research results show that the community feels that the quality of the environment is better with the existence of a conservation area so they are willing to make environmental investments; the community prioritize cheaper price as a tourist attribute that attracts them to revisit Bedengan forest ecotourism; and the community's WTP retribution (entrance ticket) is IDR 44,500 per person. The results of calculation show that the community WTP  has increased from the initial retribution set by LKDPH. The results of this research can be used as an evaluation material for LKDPH to continue maintain tourism development policies by paying attention to environmental, social and economic sustainability.